Strategy for the Development of the Investment Potential of the Tourism Industry of Ukraine in the International Economic System - TSVILIY, Sergiy M.; MYKHAILYK, Denys P.; GUROVA, Darya D.; OGLOBLINA, Viktoriia O.; KORNIIENKO, Olga M. (Theoretical and Practical Research in Economic Fields, 2024)
The purpose of this study is to establish a robust strategic framework for the development of investment potential within Ukraine’s tourism industry during the post-conflict period. The methodology involves a systematic approach encompassing literature review, conceptual framework development, measurement of corporate responsibility, creation of indicative indicators, implementation stages, and cross-border cooperation. As a result, the article presents a model of the functional platform of the international economic system, which forms the concept of the State’s investment policy on the basis of corporate socio-economic responsibility and implements the strategy of development of the tourism industry. From the standpoint of a holistic view of the strategic development of the investment potential of the tourism industry, the range of measurement of corporate socio-economic responsibility of joint investment institutions and their partnerships is presented. A methodical approach to the formation of indicative indicators of the first and second levels, which activate the investment development of the tourism industry in the regions of the country, has been developed. The stages of implementation of measures for the strategic development of the investment potential of the tourism industry in the context of international turbulence are presented. The developed proposals can be successfully implemented when planning programs for the development of the tourism industry of Ukraine on the basis of cross-border cooperation of regional associations, in order to support the national economic system of Ukraine.